Предмет: Алгебра,
автор: adeliaabdullina1
(2+х)(х2-2х+4)-1+х3 при х=1/3
Ответы
Автор ответа:
0
(2+х)(х2-2х+4)-1+х3 при х=1/3
a³ + b³ = (a + b)(a² - ab + b²)
(2+х)(х²-2х+4)-1+х³ = 8 + x³ - 1 + x³ = 2x³ + 7 = 2*(1/3)³ + 7 = 7 2/27
Если (2+х)(х²-2х+4)-(1+х³) = 8 + x³ - 1 - x³ = 7 независимо от х
Похожие вопросы
Предмет: Английский язык,
автор: ValeriaVai
Предмет: Русский язык,
автор: tuthalyan86
Предмет: Русский язык,
автор: irinkatatarint
Предмет: Русский язык,
автор: Dinara1526
Предмет: Русский язык,
автор: Арик007675